Numerical Simulation on Primary Breakup Characteristics of Liquid Jet in Oscillation Crossflow - Tao Zhang; Xinyu Song; Xingping Kai; Yeguang He; Rundong Li (Aerospace, 2023)
In order to understand the breakup characteristics of a transverse liquid jet flow in an actual combustion chamber, a numerical study was conducted using the Volume of Fluid (VOF) method combined with grid adaptation technology. The study focused on the primary breakup characteristics of liquid jets under the conditions of a steady and oscillating air crossflow. The simulated mediums were set to water and air. The research findings revealed that fluctuations in the incoming gas velocity can influence the development speed of surface waves and the mode of jet breakup during the initial stage of jet development as compared to the steady condition. In both conditions, the surface waves were initially observed to appear within 1/4 T–2/4 T. The surface wave of the jet develops faster under steady conditions because the average velocity of the steady flow is higher than that of the oscillation flow during this stage. As a result, the fragmentation of the jet is primarily influenced by the surface wave. Under an oscillating flow, the rear of the jet begins to break up earlier due to the slower development of surface waves. The velocity of the oscillating air inflow increases over time, and the speed of surface wave development also increases, gradually leading to the dominance of surface-wave-induced jet breakup. In the second stage of air inflow oscillation, an “up and down slapping” phenomenon occurs at the tail of the jet. Additionally, increasing the air inflow velocity leads to a longer jet breakup length and a higher number of droplets near the jet column. Surface waves are observed on both the windward and leeward sides of the jet. The penetration depth of the jet fluctuates with changes in the crossflow velocity, and the response of the jet penetration depth to the velocity fluctuations in the transverse air is delayed by half a period.